COMPENSATORY INTEREST SETTLEMENT AND CREDIT BANKING MORATORIUM - Avelino Sánchez, Esteban Marino (2009)
First is explained the reasons for this article, it mentions the specific legal rules that support the settlement of interest on the credit operations of companies in the financial system with end users, and then presents the average interest rates of some operations credit. Then we present the formula for calculating interest, and illustrates its application with examples 1 and 2 (the simplest). The following is, in examples 3 and 4, the calculation of interest with imputation of partial payments, if partial payments exceed the accrued interest, debt principal is reduced with each partial payment, otherwise, the principal debt remains constant, increases the debt due to accrued interest not yet paid. In such a situation, the partial payments are applied to the interest due more expensive, increases the debt due. Finally, I explain the formula for calculating simple interest, which eliminates the capitalization of interest implicit in the effective rate, where the judge had ordered to prevent anatocism.